A Systematic Literature Review on the Effectiveness of Stress Management for Teachers in Educational Settings - Yoserizal; Gistituati, Nurhizrah; Al Kadri, Hanif; Anisah (Universitas Pendidikan Ganesha, 2025)
Stress is a significant challenge that affects educators' capacity to create an optimal learning environment. This study aims to analyze the effectiveness of stress management approaches within educational settings through a systematic literature review. The research employed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) framework to identify relevant studies published in the last five years, using SCOPUS and ERIC databases. The analysis reveals that most research on educator stress management focuses on secondary and higher education levels, while studies at the junior secondary level remain limited. Unmanaged stress is found to negatively impact educators' professional performance and student learning outcomes. Effective stress management strategies include self-regulation, counseling, physical activity, adjustment of academic workload, and the use of technology to support mental health. The findings highlight the importance of comprehensive and sustainable stress management interventions to improve educators’ emotional well-being and enhance the quality of teaching and learning processes. These insights are expected to inform future educational policies and practices related to stress management.